Interaction in Creating a Harmonious Life Between the Mandar and Bugis Ethnicities in Malei Village Pedongga District, Pasangkayu Regency - Megawati, Megawati; Patta, Abdul Kadir; Cinu, Surahman; Rohim, Syaiful; Jamaluddin, Indar Ismail; Syaiful, Muhammad (Perkembangan Kajian Sosial, 2024)
The Mandar and Bugis ethnic residents have mixed together in Malei Village, Padongga District, Pasangkayu Regency, West Sulawesi Province. Social interaction has been carried out by the people of both ethnic groups to create a harmonious life. This research aims to understand the interaction of residents of the two ethnic groups in maintaining harmony while ensuring that harmonious living is a value in Malei Village. The research was carried out using descriptive qualitative methods. Informants were determined purposively as representatives of the Mandar and Bugis ethnic groups, namely community leaders, youth leaders, traditional leaders and village heads. Data analysis begins when the problem is formulated (through literature study) and continues until the research is completed. Researchers use three activity streams when analyzing, namely data condensation (selecting, focusing, simplifying and transforming field data), displaying or presenting data, and drawing conclusions or verification. The research results show that the interaction between the Mandar ethnic population and the Bugis ethnic population can be seen in associative and dissociative social interactions. Associative interactions include long-standing cooperation on various occasions, accommodation through tolerance in realizing cultural harmonization, acculturation from mixed marriages, and assimilation in the form of high respect for values ??and rules. Meanwhile, dissociative interactions through competition in the economic field, specifically in wallet nests, do not leave conflict. These aspects make the residents of Malei Village, both Mandar and Bugis, have high cultural values ??of harmony because they have a mutual respect for each other.